Identification and Prevalence of Parasites in Black Tiger Shrimp (Penaeus monodon) in Ponds of Medan Labuhan District - Yuspa Dini Rezeki; Syukriah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to identify the types and prevalence of parasites in tiger shrimp (Penaeus monodon) cultivated in ponds in Medan Labuhan District. Sampling was carried out at three semi-intensive pond locations with a total of 150 shrimp measuring 10-15 cm. Parasite identification was carried out through microscopic examination of the carapace, legs, and tail organs. In addition, pond water quality (temperature, pH, salinity, DO, ammonia, nitrate, and nitrite) was measured to assess its relationship with the presence of parasites. The results of the study found two types of parasitic protozoa, namely Epistylis sp and Zoothamnium sp with prevalences of 12.5% and 8.3%, respectively. Parasites mainly attach to the tail and legs which have fine hairs as attachment sites. Water quality analysis showed that ponds with low dissolved oxygen levels and acidic pH have a higher risk of infection. These findings emphasize the importance of water quality management, especially DO, pH, and nitrite to suppress parasite attacks and maintain the health of tiger shrimp.